Analisis Pengaruh Penggunaan Sistem Customs And Excise Information System And Automation (CEISA 4.0) Terhadap Efisiensi Proses Ekspor Pada PT. Cresco Indonesia - Hajar Tri Yudantoro; Denny Saputera (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the impact of using the Customs and Excise Information System and Automation (CEISA 4.0) on the efficiency of the export process at PT. Cresco Indonesia. PT. Cresco Indonesia, a footwear manufacturing company, transitioned from a manual system to CEISA 4.0 in 2019 to enhance efficiency in terms of time, cost, and data accuracy in the export process. This research adopts a quantitative approach with a comparative study, comparing the export process before and after the implementation of CEISA 4.0. The findings reveal that the implementation of CEISA 4.0 significantly influences time efficiency, with a reduction in the processing time for the submission of Pemberitahuan Ekspor Barang (PEB) documents until the issuance of the Nota Pelayanan Ekspor (NPE). Additionally, administrative costs for exports have significantly decreased, especially related to the reduction of document printing and transportation costs. Data accuracy in the export process has also improved, reducing the frequency of data entry errors and mitigating administrative risks. Overall, CEISA 4.0 contributes greatly to operational efficiency, with a total contribution of 96.9% towards improving export efficiency at PT. Cresco Indonesia. This study suggests that PT. Cresco Indonesia should continue to update training for staff to maximize the use of the CEISA 4.0 system and ensure infrastructure stability to support 24/7 operations. The findings also highlight the importance of digitalization in enhancing Indonesia’s product competitiveness in international markets.